De camelô a empreendedor: os “lojistas” do Shopping Popular de Cuiabá - Fonseca, Christiany Regina (Universidade Federal de São Carlos, 2021)
In the 1990s, camelôs1 who worked in the streets and squares of Cuiabá were relocated in a new space, still precarious and far from the city center. Over the years, this space has undergone transformations, guaranteeing a "mall" structure. Workers, formerly informal, are now registered and legalized, their activities have been reframed, with the entrepreneurial ideal, a term by which they have come to identify themselves. This research aimed to understand how this reframing took place, and to what extent the entrepreneurship idea was incorporated by workers, as well, as their perceptions about the galerização2 policies implemented by the government, which were questioned by them for a long time. The analytical framework sought to recover the debate on informality and its transformations in recent decades, in a context of more flexible work relations and neoliberal polices. And also, the importance of social networks to understand the strategies used by workers to stay in the activity. The workers, now small entrepreneurs, of Shopping Popular de Cuiabá (MT) were empirical. The research consisted of observation of the work, application of questionnaires to build a profile of these workersentrepreneurs and in-depth interviews. We note the internalization of the entrepreneurial ideals and the erasure of the previous history as camelôs, which is reflected, among other things, as they reinterpret the public policies of business activity.
From camelô to entrepreneur: the “shopkeepers” of Shopping Popular de Cuiabá
Keywords: Camelôs; Shopping Popular de Cuiabá; Empreendedorismo; Empresarização; Entrepreneurship; CIENCIAS HUMANAS::SOCIOLOGIA